Love somebody [compact disc] - McEntire, Reba (Nash Icon, 2015)
Country icon Reba McEntire returns with her first new album since 2010's All the Women I Am. The new album includes the hit single Pray for Peace as well as the new single Going Out Like That and a duet with Sugarland's Jennifer Nettles.